Ekološka pridelava oljk v Sloveniji - Podmenik, Dane (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2013)
The paper presents the development and characteristics of organic olive production inSlovenia. In 2012, there were 184.5 ha of organic olive orchards, which represent 10% of all olive orchards. In the coming years, we expect that the area of organic olive orchards, given the trends, could increase to 350 ha. We can resume from the research that farmers pay too little attention to sustainable agricultural practices, which raises critical reflections regarding the fulfillment of the essential standards of organic farming.
Keywords: agrarna geografija; ekološko kmetijstvo; oljkarstvo; Slovenian Istria; slovenska Istra